Formal saving in developing economies: Barriers, interventions, and effects - Sonia Beatriz Di Giannatale Menegalli; María José Roa (Inter-American Development Bank (IDB), 2016)
This paper discusses the determinants of and the barriers to formal saving both from the theoretical point of view and based on empirical evidence from various associated interventions and their possible effects at the micro and macroeconomic levels. It presents a comprehensive review of the literature based on a detailed classification of the barriers associated with supply-side factors related to access to financial products and demand-side barriers, related to the use, and frequency of use, of these products. Traditionally, the financial development literature has focused on the barriers associated with the supply of financial services that derive from high information and transaction costs. Recently published literature, however, shows how demand-side barriers, such as lack of trust, the influence of social networks, and certain cognitive biases, among other factors, might be equally important in explaining low or non-existent levels of saving. The paper concludes that such a classification and analysis of the barriers to financial inclusion leads to a deeper understanding of the question of financial inclusion and the actions that need to be taken to address it.
hdl:11319/8107
Keywords: C93; D13; D14; D91; G21; O17; 330; barriers; experimental interventions; financial inclusion; saving